Yield of SCN5A sequencing in patients with related phenotypes studied in an inherited cardiovascular diseases unit. (25th November 2020) - Rodriguez Estevez, L; Gallego Delgado, M; Villacorta Arguelles, E; Garcia Berrocal, B; Vallejo Garcia, V.E; Diaz Pelaez, E; Plata Izquierdo, B; Marcos Badillo, E; Lopez Serna, M; Alonso Fernandez De Gatta, M; Sanchez Fernandez, P.L
Abstract:  : Mutations in SCN5A gene have been associated with different cardiac manifestations, so it is frequently tested in familial cardiovascular diseases. Our objective was to analyze the prevalence of pathogenic mutations (PM) in SCN5A in hereditary cardiovascular diseases and to describe the clinical characteristics of genetic carriers. SCN5A gene (NM_198056.2) was sequenced by NGS in panels of genes directed to each cardiac phenotype. We studied 219 index cases with theses phenotypes: 144 dilated/arrhythmogenic cardiomyopathy (DCM), 34 Brugada syndrome (BS), 19 idiopathic ventricular fibrillation (IVF), 10 long QT syndrome (LQTS), 9 sudden death with nondiagnostic necropsy and 3 advanced conduction system abnormalities. We identified 8 PM in 9 families, two of them have not been previously described: deletion of exons 1–16 of SCN5A and 15_27 in SCN10A and c.2665C>G. The prevalence of PM according to phenotypes was: 3 DCM (2%), 1 IVF (5%), 4 BS (12%) and 1 advanced conduction system abnormalities (33%). Additionally, we identified 4 variants of uncertain pathogenicity, two of them in the same patient with LQTS (compound heterozygosis). The index cases description is developed in Table 1. In our cohort the prevalence of PM in SCN5A is similar to those described in literature. The majority are associated with a combined phenotype (overlap syndrome of cardiac sodium channelopathy) which is characterized by supraventricular and ventricular arrhythmias and conduction system abnormalities, and some of them with DCM. Patients with BS had no additional manifestations, apart from ventricular arrhythmias in follow up. Funding Acknowledgement: Type of funding source: None